Information credibility on the web - Yoshikiyo, Kato; Sadao, Kurohashi; Kentaro, Inui (Internet research, 2008)
As computers and computer networks become more sophisticated, a huge amount of text-based information, such as that found in web documents, emails, and business related documents, has been accumulated and circulated. Such information gives people a framework for organizing their daily life, and is starting to have a strong influence on governmental policies and business management. Our society needs technology that exploits this wealth of text-based information for a wide range of purposes: extracting credible information related to a given topic (particularly when the query has returned answe.